Sex-Specific Absolute Delta Thresholds for High-Sensitivity Cardiac Troponin T. (6th December 2021) - Liu, Li; Consagra, William; Cai, Xueya; Mathias, Andrew; Worster, Andrew; Ma, Jinhui; Rock, Philip; Kwong, Tai; Kavsak, Peter A
Abstract: Background: Sex differences in high-sensitivity cardiac troponin (hs-cTn) concentrations from healthy populations have led to the establishment of sex-specific upper reference limits for hs-cTn assays. This study assessed the performance of sex-specific delta (i.e., changes in concentrations) thresholds for the hs-cTnT assay for ruling in acute myocardial infarction (AMI) in different emergency department (ED) populations. Methods: This retrospective study consisted of 2 cohorts (Cohort 1 derivation and Cohort 2 validation). Cohort 1 consisted of 18 056 ED patients who had serial hs-cTnT measured using a 0-h/3-h algorithm at a US medical center, with Cohort 2 consisting of 1137 ED patients with 0-h/3-h sampling at a Canadian medical center. The primary outcome was AMI diagnosis with sex-specific deltas derived based on the Youden index and specificity estimates (i.e., ≥90%) in Cohort 1 and validated in Cohort 2. Results: In Cohort 1, 42% of all patients had 0-h hs-cTnT above the sex-specific 99th percentile. Males had higher 0-h hs-cTnT (median 17 ng/L) and absolute deltas (median 2 ng/L) than females (0-h median 11 ng/L, P < 0.0001; deltas median 1 ng/L, P < 0.0001) in non-AMI patients but not in patients with AMI. For ruling in AMI, the sex-specific delta thresholds based on 90% specificity (14 ng/L for males, 11 ng/L for females) performed best and resulted in 91% diagnostic accuracy in both males and females. The sex-specific delta thresholds yielding high specificity estimates were confirmed in the validation data set. Conclusions: Sex-specific absolute delta thresholds can be used to rule in AMI and are robust across different study populations.